ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU KADER POSYANDU DALAM PELAYANAN MINIMAL PENIMBANGAN BALITA - Enny Fitriahadi (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2015)
The purpose of this study was to identify and analyze the characteristics (age, education, length becomes cadres, employment and income), knowledge, attitude, support of community leaders, health workers support. The research method research method used was survey sample. The approach used is cross sectional with an explanatory study. The sample in this research were 30 respondents. Data analysis using Chi Square formula. The findings indicate that the results of the Chi square test with CI = 95% (α = 0.05) was obtained p.value = 0.035, because p.value α then Ha accepted and Ho rejected, so it can be interpreted that there is a relationship between support officers health cadre's behavior in a child's weight minimum service in Posyandu.Keywords: cadre's behavior, minimal servicing child's weight